Effects of Sales Promotion on Consummer Buying Behavior of Food Seasoning Among Nigerian House Holds: A Case Study Of Nestle Maggi Naijapot’ - Orji, Marcus Garvey; Oyenuga, Michael; Ahungwa, Agnes Iember (Budapest International Research and Critics University, 2020)
The major concern to Nigerian companies has been how do promote made in Nigeria food products like food seasoning that has been produced in line with our local taste and culture. It is in this context that this study seeks to examine the effects of sales promotion on the consumer buying behavior of food seasoning among Nigerian households using Nestle Nigeria Plc Maggi NAIJA POT brand as a case study. The study employed cross sectional research design and the population consists of consumers of Nestle product (Maggi seasoning) in Bwari Area Council, Abuja. The sample size is 246 determined using Topman’s formula. Primary data was used through administration of questionnaire and regression analysis was used to test the relationship between the study variables. The findings revealed that most of the consumers enjoy the rebates which influence their decision before, during and after the purchase; there is a positive effect of free trial and free gift on consumer buying behavior of Maggi NAIJAPOT in Bwari Area Council, Abuja. The study concluded that that sales promotion through rebates, free trial and free gifts is one significant tool marketing companies should give attention to in order to influence their consumers’ buying behavior, and recommended among others that providing free samples for food seasoning is a good technique to use in introducing new products to the Nigerian marketplace, also free gift should be included in the outer part of the product packaging to serve as a visual attraction to Nigerian consumers. It may also take the form of the commonly used terminology BOGOF’ (Buy one get one free)